Smoking Prevention and Cessation - Rajer, Mirjana (IntechOpen, 2018)
Smoking was and remains one of the most important public healthcare issues. It is estimated that every year six million people die as a result of tobacco consumption. Several diseases are caused or worsened by smoking: different cancer types, heart disease, stroke, lung diseases and others. In this book we describe the different toxic effects of smoke on the human body in active and in passive smokers. It is also well known that many people who smoke wish to quit, but they rarely succeed. Smoking prevention and cessation are of utmost importance, thus we also describe different strategies and aspects of these issues. We hope that this book will help readers to understand better the effects of smoking and learn about new ideas on how to effectively help other people to stop smoking.